Local Online Courier and Ride-Hailing Service Social Media Marketing - Ilyas Lampe; Raisa Alatas; Nifi Orynka; Gemilang Bayu Ragil Saputra (Komunikator, 2021)
Topokeni was a local online courier and ride-hailing service in Palu. In this study, we tried to understand the social media marketing strategies used by Topokeni, as we assumed that Topokeni had specific strategies to compete with national and international scale ride-hailing services such as Grab and Gojek. Thus, this study was focused and aimed to understand and describe the Instagram marketing strategies of Topokeni based on four aspects of social media marketing in a qualitative-case study approach. Data were collected through in-depth interviews, observations, and document study on social media and other relevant archives. The results showed that social media became an alternative to survive and increase tenants and consumers. In the context aspect, Topokeni admins used nicknames such as kakak (bro/sis) to their customers to reach broader targets. In the communication aspect, Topokeni used graphic elements in photos, videos, infographics, and testimonials posts. In the collaboration aspect, Topokeni merged the tenant’s market with Topokeni’s customers. In the connectivity aspect, Topokeni synergized the contents, themes, and brand positioning using #kurirpalu and #deliverypalu, also @(mention) feature on partner tenant accounts and personal customers as a form of appreciation and responsibility.